Relationship between volleyball spike jump height and lower limb kinetics is stronger for orientation leg than rear leg - Makino, M.; Nakahara, T.; Nagakubo, K.; Ando, Y.; Tauchi, K. (Sports Biomechanics, 2025)
The orientation and rear legs have different roles in the spike jump (SPJ) in volleyball, yet the relationship between the jump height and kinetics of each leg remains underexplored. We aimed to clarify the relationships between jump height and kinetics of the orientation and rear legs in the SPJ. This study included 18 female college volleyball players. The experimental trial comprised an SPJ with a three-step run-up. The motion and ground reaction forces were measured using eight high-speed cameras and two force plates. Kinetic variables from the last foot contact to take-off were calculated, and their relationship with jumping height was examined. The results showed that the peak joint torques for ankle plantar flexion (r = 0.562, p = 0.015), hip extension (r = 0.684, p = 0.002), and hip abduction (r = 0.670, p = 0.002) of the orientation leg were significantly positively correlated with jump height. No significant correlations were found for the rear leg, except for the hip abduction torque (r = 0.538, p = 0.021). These findings indicate that interindividual difference in jump height are more strongly related to the kinetics of the orientation leg than those of the rear leg after final rear foot contact.